Optimizing pectin lyase production using the one-factor-at-a-time method and response surface methodology - Gul, Ertugrul; Dursun, Arzu Yadigar; Tepe, Ozlem; Akaslan, Gonca; Pampal, Fadile Gul (Wiley, 2025)
Pectinases are commonly industrially synthesized by molds. This study aimed to optimize pectin lyase synthesis by a bacterium, Pseudomonas fluorescens, using both the one-factor-at-a-time (OFAT) method and response surface methodology. First, on optimization of pectin lyase fermentation by the OFAT method, the effects of pectin, peptone, yeast extract, (NH4)(2)SO4, pH, and salts were investigated. The highest pectin lyase activity was determined to be 28.63 U/mL at pH 8, 30 degrees C, with 1% (w/v) pectin and 0.14% (w/v) (NH4)(2)SO4 concentration at the 90th hour. The effect of substrate inhibition on the microbial growth was also investigated, and the results showed that the process can be described by noncompetitive inhibition model. The values of kinetic constants were determined as mu (m) = 0.175 h(-1), K-S = 6.931 g/L, and, K-I = 6.932 g/L by nonlinear regression analysis. It was reported that pectin lyase enzymes exhibited peak activity at 50 degrees C and pH 8. Finally, response surface methodology (RSM) was utilized to optimize pH, concentrations of ammonium sulfate, and pectin, which were chosen as independent variables. The interactions between these variables were also examined. According to RSM, the optimum values of the parameters to achieve a maximum pectin lyase activity of 35.62 U/mL were determined to be pH 7.97, 1.25% (w/v) pectin concentration, and 0.25% (w/v) (NH4)(2)SO4 concentration.
Keywords: enzyme stability; microbial kinetic; optimization; pectin lyase; Pseudomonas fluorescens; response surface methodology